SIGNIFIKANSI AMERIKA SERIKAT DI WTO DALAM KASUS ANTI DUMPING AYAM BROILER TIONGKOK - Bayu P, Nyoman Bagus; Sushanti, Sukma; Suwecawangsa, Putu Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   China's inability to meet domestic needs of broiler chickens, encourages trade cooperation with the United States. United States exports of broiler chicken commodities to China continue to increase every year. Until 2010, United States exports to China dropped by 85%. China accuses the United States of having carried out dumping actions on broiler chicken products.In response, United States submitted this case to be resolved through the Dispute Settlement Body WTO (World Trade Organizations). This study aims to analyze how significance the United States in WTOrelated to trade disputes with China in the case of broiler chicken exports in 2010-2014. The concept used in this study refers to the concept of International Organizations by Clive Archer (2001) and the concept of Power in International Organizations by Barkin (2006). Keywords: Dumping, Dispute Settlement Body, United States, China.